Clinical and functional vulnerability of elderly caregivers of older adults with Alzheimer's - Maria Emilia Marcondes Barbosa; Ellen Vanusa Martins Bertelli; iovana Aparecida de Souza Scolari; Marciane Conti Zornita Bortolanza; Ieda Harumi Higarashi; Lígia Carreira (Universidade Federal do Ceará, 2019)
Objective: to evaluate the clinical and functional vulnerability of elderly caregivers of older adults with Alzheimer's disease. Methods: it was a cross-sectional study with elderly caregivers registered in an Alzheimer's Patient Care Association. A sociodemographic questionnaire and the Clinical-Functional Vulnerability Index-20 were used for data collection, which were analyzed using R statistical software, Spearman's correlation, and Somers' D. Results: 31 elderly caregivers participated, mostly women, aged between 60 and 74 years, married, with low schooling, and taking care of the spouse. A greater risk of vulnerability related to self-perceived health, cognition and mood was identified. Functionality in daily activities, communication, mobility, and multiple comorbidities was preserved. Conclusion: most elderly caregivers were at risk of frail, which did not stop them from providing care for the relative with Alzheimer's. Professionals and institutions should work to prevent the functional decline of these elderly caregivers.